Buya Syafii dan Bangsa yang Oleng: Sebuah Refleksi - Hasyim, Mustofa W (MAARIF Institute, 2023)
Prof. Dr. Ahmad Syafii Maarif or Buya Syafii has matured in personality and has relatively advanced knowledge because of the long process that he has not gone through easily. Experiencing a life episode that has many bitterness to a life that has a lot of sweetness, from being a school magazine writer, journalist and editor of party magazines, mass organization magazines, to being a teacher, manual worker, chicken and goat trader, to being a lecturer and struggling as hard as he can to climb the educational ladder until he gets doctoral degree and was confirmed as a professor of history at his campus. He once held the top position in the Muhamamdiyah Association, as General Chair, and held the position as General Leader of Suara Muhammadiah until the end of his life. Buya Syafii received the provisions to participate in dressing up or improving the lives of the Islamic Ummah and the Indonesian nation because he had studied and studied the world of thought of Muhamamd Iqbal and Fazlur Rahman and absorbed many role models from his seniors at Muhammadiyah and fellow Indonesian intellectuals and other national figures. Including his friendship with Gus Dur and leaders across religions and groups. Buya Syafii was very concerned when he saw something swaying. Including when he witnessed for himself the symptoms of a nation faltering which made him called to do and say things to improve the situation.